Labour management of construction site (labour welfare) / Nurul Salwani Noor Yakim - Noor Yakim, Nurul Salwani (Faculty of Architecture, Planning and Surveying, 2010)
Construction site is a place specially prepared to carry out activities of a project. Construction site is a place that has the potential to occur any accident or minor accidents such as slipping or injury. To make sure labour management at construction site is carried out accordance to legal requirement or not, an assessment was conducted to five case studies in Kuala Lumpur and Shah Alam. To achieve the objectives, assessment is carried out by observing condition around the construction site, taking pictures and distributing questionnaire. Questionnaire provided in connection with occupational safety and welfare of workers on site. The findings are then stipulated based on the analysis or percentage of the total data obtained from the questionnaire distributed and finally the recommendation are made to the problems associated with the management aspects of workers on site.